Networks, Propinquity, and Innovation in Knowledge-intensive Industries - Whittington, Kjersten Bunker; Owen-Smith, Jason; Powell, Walter W. (Administrative Science Quarterly, 2009)
Industrial districts and regional clusters depend on the networks that arise from reciprocal linkages among co-located organizations, while physical proximity among firms can alter the nature of information and resource flows through networks. We consider the joint effects of geographic propinquity and network position on organizational innovation using negative binomial count models of patenting activity for U.S.-based life science firms in industrial districts and regional clusters across a 12-year time period, 1988–1999. We find evidence that regional agglomeration and network centrality exert complementary, but contingent, influences on organizational innovation. Results show that in the high-velocity, research-intensive field of biotechnology, geographic and network positions have both independent and contingent effects on organizational innovation. The influence of centrality in local, physically co-located partner networks depends on the extent to which firms are also embedded in a global network comprising physically distant partners. Such global centrality, however, alters how proximity to two important classes of organization-other biotechnology firms and public sector research organizations, such as universities, research institutes, and teaching hospitals—influences innovation. Regional agglomeration shapes the character of information and resource flows through networks, while much of what makes industrial clusters region-like involves the structure of their internal networks. We conclude that network effects persist both independently and interdependently with geographic variables, and regional characteristics influence the degree to which centrality enhances innovation.